Implementasi Pembiayaan KPR iB Hijrah dengan Akad Murabahah dan Musyarakah Mutanaqishah pada Perbankan Syariah : Studi Kasus pada Bank Muamalat KCP Rancaekek - Adila Permatasari; Dudang Gojali (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Islamic banking plays a crucial role in providing financing in accordance with Islamic principles, including through the Home Ownership Credit (KPR) product. This study aims to analyze the implementation of the Murabahah and Musyarakah Mutanaqishah (MMQ) contracts in the iB Hijrah KPR financing product at Bank Muamalat KCP Rancaekek. The Murabahah contract is implemented through a sale and purchase mechanism, where the bank purchases the house the customer needs and resells it with an agreed profit margin, thus providing price certainty and a simple process. Meanwhile, the MMQ contract is based on a partnership between the bank and the customer with a concept of joint ownership that gradually decreases, thus creating flexibility and a more balanced risk sharing. This study uses a qualitative descriptive approach with data collection techniques through literature studies, interviews, and observations. The results of the analysis show that the majority of customers prefer the Murabahah contract due to its simplicity, although in the long term, MMQ is seen as more economical and fair. Thus, both contracts are equally relevant to support Sharia-based home ownership. This research is expected to contribute to Islamic banking in improving service quality, strengthening Islamic financial literacy, and encouraging innovation in competitive and sustainable financing products.